Molecularly Imprinted Polymer (MIP): A Promising Recognition System for Development of Optical Sensor for Textile Dyes. (2017) - Foguel, Marcos Vinicius; Pedro, Natacha Thaisa Bello; Zanoni, Maria Valnice Boldrin; Sotomayor, Maria del Pilar Taboada
Abstract: An alternative for determination of dyes is the biomimetic sensors development with optical transduction, employing molecularly imprinted polymers (MIP) as recognition system. This work shows the MIP synthesis for the textile dye Acid Green 16 and the results of rebinding, selectivity and application of this MIP in textile effluent. The imprinted polymer presented rebinding of 83% and imprinted factor of 6.91, great selectivity and recovery next to 100%. Due to the excellent performance of this MIP, it can be a promisingsynthetic recognizer in the development of optical biomimetic sensors based on optical fibers.